Nilai-nilai Aqidah Akhlak dalam Novel Nyala Semesta - Siti Maratush Sholihah; Muhammad Munadi (UIN Mataram, 2021)
The values ??of aqidah and morals can be found in print-based secondary learning resources, namely novels. Meanwhile, ideally the values ??of aqidah akhlak can be found in primary and exemplary learning resources. So, this study analyzes the values ??of aqidah and morals contained in the novel Nyala Semesta. This research is a library research with data collection techniques is documentation and interviews. The validity of the data in this study is a contingency technique and source triangulation. Meanwhile, the data analysis used content analysis of the types is characteristics. The results of the study indicate that there are values ??of aqidah in the novel Nyala Semesta, namely faith in Allah SWT in terms of the nature and af'al of Allah SWT, namely rububiyah and uluhiyah and the value of faith in Al-qur’an. In addition, there is the value of Allah's denial by Mushab figures. Moral values ??consist of morals towards Allah SWT by loving Allah SWT, jihad, dhikr and prayer, tawakkal, husnudzan and gratitude. Morals towards the Messenger of Allah are to love and follow/ittiba' Rasulullah SAW and blessings. Morals towards oneself by seeking knowledge, istiqomah, earnest and simple. Morals towards the family are loving family members, being devoted to both parents. Morals towards others consist of helping others, being friendly and maintaining ukhuwah Islamiyah.Key Words: Aqidah, Akhlak, Value, Novel, Nyala Semesta